Enhancement in rate of photocatalysis upon catalyst recycling - Sorathiya, Kalpesh; Mishra, Biswajit; Kalarikkal, Abhishek; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S.; Khushalani, Deepa (Scientific Reports, 2016)
Recyclability is an important aspect for heterogeneous photo-catalysts. Ease of recovery and stability of the photo-catalyst in terms of efficiency over the number of cycles are highly desired and in fact it is ideal if the efficiency is constant and it should not decrease marginally with each cycle. Presented here is a seminal observation in which the photocatalytic activity is shown to improve with increasing number of catalytic cycles (it is 1.7 times better after the 1st cycle and 3.1 times better after the 2nd cycle). Specifically, nanorods of pure TiO2 and TiO2 doped with controlled amount of tungsten have been used to degrade two model pollutants: Phenol and Rhodamine B under exclusive visible light illumination. It was found that, in case of 1 mol.% W incorporation, rate of photocatalysis and also the range of visible light absorption of the photocatalyst increased after the photocatalysis as compared to before photocatalysis. This aspect is unique for doped TiO2 and hence provides an intriguing way to mitigate low photoactivity.